chromDraw: an R package for visualization of linear and circular karyotypes - Janečka, Jan; Lysak, Martin A (Chromosome research, 2016)
Species-specific sets of chromosomes-karyotypes-are traditionally depicted as linear ideograms with individual chromosomes represented by vertical bars. However, linear visualization has its limitations when the shared collinearity and/or chromosomal rearrangements differentiating two or more karyotypes need to be demonstrated. In these instances, circular visualization might provide easier comprehension and interpretation of inter-species chromosomal collinearity. The chromDraw graphical tool was developed as a user-friendly graphical tool for visualizing both linear and circular karyotypes based on the same input data matrix. The output graphics, saved in two different formats (EPS and SVG), can be easily imported to and modified in presentation and image-editing computer programs. The tool is freely distributed under GNU General Public License (GPL) and can be installed from Bioconductor or from the chromDraw home page.
Keywords: Software; karyotyp; software; karyotypizace; Chromosomes; chromozomální aberace; R; Visualization; Chromosome Aberrations; Karyotype; Chromosome; Karyotyping; chromozomy